2015
DOI: 10.3928/00220124-20151020-05
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of New Nurses Concerning Incivility in the Workplace

Abstract: The participants witnessed uncivil interactions that negatively impacted them emotionally, professionally, and physically. They also discussed the harmful effects of incivility on patients, whose care may be impeded or their faith in caregivers eroded in hostile, uncivil care environments. Nurses in professional development play a crucial role in promoting a culture of civility through raising awareness, supporting nurses new to the profession, and helping health care workers to better cope with incivility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 18 publications
0
38
1
Order By: Relevance
“…New graduate nurses working in community health reported significantly higher authentic leadership (M=2.99, SD=.97) than NGNs in medical surgical (M=2. 57,SD=.84) or critical care (M=2.52, SD=.91) units. In addition, there were significant (p<.05)…”
Section: Relationship Of Demographic Variables To Major Study Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…New graduate nurses working in community health reported significantly higher authentic leadership (M=2.99, SD=.97) than NGNs in medical surgical (M=2. 57,SD=.84) or critical care (M=2.52, SD=.91) units. In addition, there were significant (p<.05)…”
Section: Relationship Of Demographic Variables To Major Study Variablesmentioning
confidence: 99%
“…Although supervisor incivility is less frequent than other sources, it has been linked to poor mental health (Laschinger, eal., 2013) and lower nursing productivity and commitment (Lewis & Malecha, 2011). A qualitative study of incivility experiences of NGNs showed 10% of the participants witnessed disrespect from their leaders; they also described leader behaviours such as not fulfilling their promises, shouting at staff in front others, making false accusations as well as unfairly treating their staff (Kerber, Woith, Jenkins & Astroth, 2015). Uncivil behaviours negatively influence staff leader-nurse relationships by showing disrespect toward others and marginalizing them within their group (Embree & White, 2010).…”
Section: Study Targeted Employees Of Northmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these points and in an attempt to promote patient safety, The Joint Commission (2008) put forth a zero tolerance for intimidating behaviors among hospital staff [6]. Nurses report that incivility negatively impacts patients by impeding and delaying care and disrupting patients' faith in the staff [7]. It is evident that incivility continues to pose a threat to both nursing staff and patients.…”
mentioning
confidence: 99%
“…Bullying is regrettably common in health care; in a survey by the Joint Commission for the Accreditation of Healthcare Organizations (2002), 90% of nurse respondents had witnessed some form of bullying behavior. Bullying behavior increased workload, prevented meeting patients' needs, and inhibited meeting the faith needs of patients (Kerber et al, 2015).…”
Section: Introductionmentioning
confidence: 99%